TORAKOCHIRURGIAA single-center experience in surgical treatment of squamous cell oesophageal carcinoma in the years 1970–2007 - Zieliński, Jacek; Świerblewski, Maciej; Kruszewski, Wiesław J.; Jaworski, Radosław; Haponiuk, Ireneusz; Irga, Ninela; Kopacz, Andrzej; Jaśkiewicz, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Squamous cell oesophageal carcinoma is a malignant tumor with very bad prognosis, caused among other factors also by generally advanced stage of the disease at the moment of diagnosis. It is estimated that only up to 40% of patients can be qualified for surgical treatment, which is considered to be the gold standard of clinical management. Aim : The aim of the work was to present experience of a single clinical center in surgical management of squamous cell oesophageal carcinoma in the years 1970–2007. Material and Methods : 815 patients were treated surgically for squamous cell oesophageal carcinoma in the Department of Oncological Surgery in Gdansk in the years 1970–2007. Analysis of clinical and demographic data, types of surgical methods, markers of tumor respectability, post-operative mortality rate, short and long term complications of the treatment and overall survival rates was performed for two periods of time: 1970–1990 and 1991–2007. Results : In the first period of time the respectability ratio for patients undergoing surgery for squamous cell oesophageal carcinoma was 28.8% (122 radical surgeries and 302 palliative surgeries) while in the second period of time the ratio was 42.5% (166 radical surgeries and 225 palliative surgeries; p < 0.001). Postoperative mortality rate for the years 1970–1990 was 29.2% while for the years 1991–2007 it was 4.8% (p < 0.001). Complications in the postoperative period were more frequent in the first of the analyzed periods. 5-years overall survival raised from 7.8% for the patients undergoing radical surgery in the years 1970–1990 to 18.1% for patients treated in the years 1991–2007. Conclusions : Improvement in the results of surgical treatment of squamous cell oesophageal carcinoma patients was achieved owning to formation of an experienced surgical team, better preparation of the patients to the surgery, introduction of novel types of surgical management and tightening criteria of qualification for surgical treatment. Despite the improvements, long-term prognosis for squamous cell oesophageal carcinoma remains poor.